Combined miRNA and mRNA sequencing reveals the defensive strategies of resistant YHY15 rice against differentially virulent brown planthoppers - Yu, Bin; Geng, Mengjia; Xue, Yu; Yu, Qingqing; Lu, Bojie; Liu, Miao; Shao, Yuhan; Li, Chenxi; Xu, Jingang; Li, Jintao; Hu, Wei; Tang, Hengmin; et al. (Frontiers in Plant Science, 2024)
The brown planthopper (BPH) poses a significant threat to rice production in Asia.The use of resistant rice varieties has been effective in managing this pest. However, the adaptability of BPH to resistant rice varieties has led to the emergence of virulent populations, such as biotype Y BPH. YHY15 rice, which carries the BPH resistance gene Bph15, exhibits notable resistance to biotype 1 BPH but is susceptible to biotype Y BPH. Limited information exists regarding how resistant rice plants defend against BPH populations with varying levels of virulence. In this study, we integrated miRNA and mRNA expression profiling analyses to study the differential responses of YHY15 rice to both avirulent (biotype 1) and virulent (biotype Y) BPH. YHY15 rice demonstrated a rapid response to biotype Y BPH infestation, with significant transcriptional changes occurring within 6 hours. The biotype Y-responsive genes were notably enriched in photosynthetic processes. Accordingly, biotype Y BPH infestation induced more intense transcriptional responses, affecting miRNA expression, defense-related metabolic pathways, phytohormone signaling, and multiple transcription factors. Additionally, callose deposition was enhanced in biotype Y BPH-infested rice seedlings. These findings provide comprehensive insights into the defense mechanisms of resistant rice plants against virulent BPH, and may potentially guide the development of insect-resistant rice varieties.